Manifestations of tragedy in elegy of loved ones of Al-Mutanabbi (Damascus University Journal of arts and humanities sciences, 2025)
Tragedy, as an aesthetic value, is based on the opposition between will and inevitability in the midst of a tragic hero's struggle against an inescapable and irreversible force. While we feel awe in the face of this overwhelming force, whose magnitude exceeds our ability to comprehend it, we also feel respect for the hero who confronts it and pity for his inevitable fate, which in one way represents a defeat for life.In elegies, this overwhelming force is often represented by death, and if conflict is the essence of tragedy. The tragic specificity of Al-Mutanabbi’s elegies stems from the nature of this conflict, which is clearly evident in Al-Mutanabbi’s position on death and its adoption of various forms in those elegies.By examining the elegiac poems in Abu Tayeb’s collection, which express his emotional experiences regarding the death of loved ones andin which the value of tragedy is evident, we are drawn to three characters who wrote poems that are considered among the finest examples of elegiac poetry: his poem in mourning for his grandmother, his poem in mourning for Khawla, the sister of Sayf al-Dawla, and his poems in mourning for Abu Shuja’ Fatik.The study adopted a descriptive and analytical approach to the texts of the study, in light of the concepts of aesthetics. It reached a number of conclusions, the most prominent of which are: The death of loved ones is manifested in Al-Mutanabbi's elegies as a chapter in the ongoing conflict between Al-Mutanabbi and time. The aesthetic values ​​of the sublime, the delicate, the heroic, and the sublime intertwine in the manifestation of the tragic in Al-Mutanabbi's elegies and the deepening of its emotional impression in the recipient's soul.
Keywords: Tragic; Sublime; Lament of The Beloved; Al-Mutanabbi